Women in Earth Science / Geology Departments of Canadian Universities: 1983-1992 - Pe-Piper, Georgia (Geoscience Canada, 1994)
Abstract The proportion of female students in Canadian earth science/geology departments has increased slowly in the past decade, from 20% to 28% at theB.Sc. and M.Sc. levels and at the Ph.D.level (based on small numbers) from 8%to a peak of 21 % in 1991. The proportion of female faculty remains at less than 5% and only 13% of new faculty hirings since 1983 have been women. The sepercentages are similar to those in other physical science disciplines; theyare higher than those in the UnitedKingdom, but lower than those in theUnited States. Vigorous action is required both at the elementary/high school and university levels to avoid wasting female talent and to ensure that female undergraduate students have role models among graduate students and faculty.